Kingdom of Lesotho : Poverty Reduction Strategy Paper; Joint Staff Advisory Note. (IMF Staff Country Reports; Country Report ;, 2006)
The Kingdom of Lesotho's Poverty Reduction Strategy Paper reports that consistent implementation of sound macroeconomic policies is critical to the attainment of poverty reduction objectives. At the central level, the authorities established sector working groups to facilitate the formulation of informed policies that respond to the identified priorities. To deal with cross-cutting issues, thematic groups have been established. The private sector, despite weak organizational capacity at the beginning, made a significant contribution to the preparation of the Poverty Reduction Strategy.